Signature of the Stratosphere-Troposphere Coupling on Recent Record-Breaking Antarctic Sea-Ice Anomalies - Cordero-Carrasco, R; Christin-Feron, S (Copernicus Publications, 2023)
In February 2023, the sea-ice extent around Antarctica dropped to 1.79×106km2, setting a satellite-era record low for the second straight year. Recent records stress the need for further research into the factors behind record-breaking Antarctic sea-ice anomalies. By influencing the circumpolar westerly winds, the stratospheric polar vortex has played a major role in the Antarctic surface climate in recent decades. However, the footprint of the polar vortex variability in the year-To-year changes in the Antarctic sea-ice cover remains obscured. Here, we use satellite retrievals and reanalysis data to study the response of the sea-ice extent around Antarctica to changes in the polar vortex strength. We focus on the last 2 decades that saw sharp changes in the stratospheric zonal flow, the tropospheric westerly winds and the sea-ice cover (the latter climbed to record highs in 2013 and 2014 before dropping to record lows in 2017, 2022 and 2023). Our results suggest that this unprecedented interannual variability is noticeably influenced by the polar vortex dynamics. The signature of the stratosphere-Troposphere coupling is apparent in recent records (highs and lows) in the sea-ice extent around Antarctica. © 2023 Raúl R. Cordero et al.